Review of Defective NADPH Oxidase Activity and Myeloperoxidase Release in Neutrophils From Patients With Cirrhosis - Moreau, Richard; Périanin, Axel; Arroyo, Vicente (Frontiers in Immunology, 2019)
Patients with decompensated cirrhosis are highly susceptible to develop bacterial infections and these can trigger multiorgan failure associated with high in-hospital mortality. Neutrophils from patients with decompensated cirrhosis exhibit marked alterations that may explain the susceptibility of these patients to develop bacterial infections. These neutrophil alterations include marked defects in intracellular signaling pathways involving serine/threonine kinases such as protein kinase B (AKT), p38 mitogen-activated protein kinase (MAPK), and the MAP kinases1/2; activation of the NADPH oxidase complex; myeloperoxidase (MPO) release; and bactericidal activity of neutrophils stimulated by the bacterial peptide formyl-Methionine-Leucine-Phenylalanine (fMLF). Decreased activity of the NADPH oxidase complex is related to reduced levels of expression of its major components through posttranscriptional mechanisms. A defect in the protein kinase B (AKT) and p38 mitogen-activated protein kinase (MAPK)-mediated signaling pathways may explain the decrease in phosphorylation of p47phox (an important component of the NADPH oxidase complex) and MPO release, in response to fMLF stimulation. Most of these alterations are reversible ex vivo with TLR7/8 agonists (CL097, R848), raising the possibility that these agonists might be used in the future to restore neutrophil functions in patients with cirrhosis.